Determination of Growth Performance of Mandarin (Citrus reticulata Blanco) in Relation to Surrounding Chir pine (Pinus roxburghii Sarg.) at Dagana District Through Dendrochronological Analysis - Nidup, Dorji; Khandu, Yeshey; Dendup, Tashi; Chozang, Jigme; Wangmo, Ugyen (International Journal of Environment, 2024)
Tree-ring growth is closely related to climate and the environmental changes during the growth period; thus, it can record precise information on climate variations. This study aimed to understand radial growth changes and develop tree-ring chronologies of Citrus reticulata, validated by tree-ring chronologies of Pinus roxburghii within the same micro-site. Tree-ring data were obtained from the sample cores collected from the two different altitudinal sites (1,150 to 1,250 masl) 400 to 500 m apart and compared to the climate data from Drujeygang meteorological station. Using dendroclimatological methods, summary statistics were obtained through cross-dating and standardization, and tree-ring chronology was written. Ring-width chronologies spanning 36 to 41 years were developed for C. reticulata and 57 to 174 years for P. roxburghii. One-way ANOVA test analysis showed spatial patterns of variability within the altitudinal range of 1,150 to 1,250 masl. Correlation analysis indicated that the growth of C. reticulata was highest at the mean annual temperature range of 19.0 to 19.4°C and mean precipitation range of 86.51 to 147.45 mm. C. reticulata showed a positive relationship with mean annual temperature and precipitation, and in contrast, P. roxburghii showed a negative relationship. However, the growth variability of both C. reticulata and P. roxburghii in both regions depicted the remarkable variability due to fluctuating climatic factors. This study evaluated the relationship between tree-ring growth and climate factors and is expected to contribute to the understanding of changes in productivity, which will be affected by climate change in the future.